THE PHOTOMETRIC INVESTIGATION OF THE ACTIVE POST-NOVA CP LAC IN HIGH AND LOW STATE OF BRIGHTNESS IN 2006-2008 YRS - Litvinchova, A. A.; Pavlenko, E. P. (Одеські астрономічні публікації, 2010)
We present the result of investigations of the quasi-periodic and periodic light variations of the CP Lac connected with different sources in the binary system. We found that CP Lac in 2006 was brighter on ∼ 1m in comparison with 2008. The amplitude of the light variations in 2006 is growing with decreasing of the wave-length. The amplitude in B = 0m.3, in V = 0m.2. The mean brightness of CP Lac in 2008 varies from night to night during all interval of observation with amplitude 0m.5 in unfiltered light. Data of observations in 2006-2008 have a general period 0.037(5) day that is possibly related to the period of rotation of white dwarf.